Paternal epigenetic influences on placental health and their impacts on offspring development and disease - Bhadsavle, Sanat S.; Golding, Michael C. (Frontiers in Genetics, 2022)
Our efforts to understand the developmental origins of birth defects and disease have primarily focused on maternal exposures and intrauterine stressors. Recently, research into non-genomic mechanisms of inheritance has led to the recognition that epigenetic factors carried in sperm also significantly impact the health of future generations. However, although researchers have described a range of potential epigenetic signals transmitted through sperm, we have yet to obtain a mechanistic understanding of how these paternally-inherited factors influence offspring development and modify life-long health. In this endeavor, the emerging influence of the paternal epigenetic program on placental development, patterning, and function may help explain how a diverse range of male exposures induce comparable intergenerational effects on offspring health. During pregnancy, the placenta serves as the dynamic interface between mother and fetus, regulating nutrient, oxygen, and waste exchange and coordinating fetal growth and maturation. Studies examining intrauterine maternal stressors routinely describe alterations in placental growth, histological organization, and glycogen content, which correlate with well-described influences on infant health and adult onset of disease. Significantly, the emergence of similar phenotypes in models examining preconception male exposures indicates that paternal stressors transmit an epigenetic memory to their offspring that also negatively impacts placental function. Like maternal models, paternally programmed placental dysfunction exerts life-long consequences on offspring health, particularly metabolic function. Here, focusing primarily on rodent models, we review the literature and discuss the influences of preconception male health and exposure history on placental growth and patterning. We emphasize the emergence of common placental phenotypes shared between models examining preconception male and intrauterine stressors but note that the direction of change frequently differs between maternal and paternal exposures. We posit that alterations in placental growth, histological organization, and glycogen content broadly serve as reliable markers of altered paternal developmental programming, predicting the emergence of structural and metabolic defects in the offspring. Finally, we suggest the existence of an unrecognized developmental axis between the male germline and the extraembryonic lineages that may have evolved to enhance fetal adaptation.